Pengaruh Pembelajaran Matematika Metode Gasing Terhadap Hasil Belajar Penjumlahan Bilangan Cacah Siswa Kelas 3 SD - Rara Dini Alianti; Vira Febrianty; Kowiyah Kowiyah (International Forum of Researchers and Lecturers, 2024)
The main reason underlying this research is that many students feel that mathematics is a difficult subject, which leads to low learning outcomes in this subject. This research aims to explore the influence of the spinning top learning method on the addition of whole numbers in class III students in elementary schools. Using a quantitative experimental research design, data was obtained through pre-test and post-test to evaluate student skills. The results of the analysis show that the application of the top method significantly improves student learning outcomes, with the average post-test score being higher than the average pre-test score. From this research, it can be concluded that: (1) The mathematics learning method used has proven to be very effective. (2) The test results show an increase in students' mathematical abilities. (3) The spinning top method has a positive impact in improving mathematics learning skills, especially for class III students. This research also shows that this method has proven effective in increasing motivation. and students' understanding of mathematical concepts.